Character education in the family as a strengthening of moderation during the pandemic era - Suherman Suherman (Journal of Social Studies (JSS), 2022)
This paper is the result of research carried out find the character education activities in the family environment to support moderation during the pandemic era. This study was conducted to determine the location of the Babussalam Langkat family and community. In this study, 50 parents participated as respondents, while questionnaires, interviews, documentation, and in-depth observations were also used to collect data. After reviewing the data from the questionnaire responses of 50 parents, the results of interviews with numerous parents and students (adolescents), Teachers, and the Village Head, as well as observational data, conclusions of the data were made. Particularly, this study identified a number of character education activities in the Babussalam village of Langkat Regency. During the pandemic, the residents of Babussalam, who are practitioners of the Naqsyabandiyah congregation, have provided character education to their families, and even Babussalam village itself has existed for a long period of time. The methods and patterns of how parents educated their children are: habituation, guidance, example, unity, communicativeness, affectionateness and gentle, consistency, commitment, togetherness and deliberation. Religious character, compassion, affection, responsible, respect and honor for teachers and parents, devoted to study, interactive and friendly, compact and helpful as well as deliberate are among the qualities fostered in students (children). All of these characters have contributed in the consolidation of Wasyatiyah Islam and Muslim communities who practice moderation in religion.